Analysis of Antibiotic Use In Ispa Patients At Uptd. Tanah Luas Community Health Center, North Aceh Regency - Sri Wastuti; Nurhasanah Rumanda; Tasya Humaira (International Journal of Health Engineering and Technology, 2025)
Upper respiratory tract infection (URTI) is an acute infection that attacks the nose, paranasal sinuses, pharynx, trachea, bronchi, lungs, and epiglottis. Bacteria, viruses, and microbes are the causes of URTI. Antibiotics are the most widely used class of drugs to treat infections. This study aims to determine the rationality of the use of antibiotics used by patients with upper URTI at the Tanah Luas Health Center, North Aceh Regency based on the right indication, right drug selection, right dose, and right patient. This type of research is a non-experimental study with a descriptive analytical research type. Data collection was carried out retrospectively on patient medical records. Data were obtained by analyzing data on the distribution of age, gender, antibiotic therapy, right indication, right drug, right dose and right patient. The results of this study indicate the rationality of antibiotic use in outpatient URTI patients at the UPTD Tanah Luas Health Center, North Aceh Regency, seen based on the criteria of right indication of 100%, right dose of 100%, right drug of 100%, and right patient of 100%.